2016
DOI: 10.1016/j.nbd.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of glymphatic fluid transport in a mouse model of Alzheimer's disease

Abstract: Glymphatic transport, defined as cerebrospinal fluid (CSF) peri-arterial inflow into brain, and interstitial fluid (ISF) clearance, is reduced in the aging brain. However, it is unclear whether glymphatic transport affects the distribution of soluble Aβ in Alzheimer’s disease (AD). In wild type mice, we show that Aβ40 (fluorescently labeled Aβ40 or unlabeled Aβ40), was distributed from CSF to brain, via the peri-arterial space, and associated with neurons. In contrast, Aβ42 was mostly restricted to the peri-ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
393
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 437 publications
(460 citation statements)
references
References 76 publications
20
393
2
2
Order By: Relevance
“…However, their method does not distinguish between impaired membrane transport of Ab (4) and impaired CSF clearance, which carries the Ab. Suggesting CSF clearance abnormalities in AD, impaired glymphatic CSF clearance was recently observed in aged wild-type mice (5) and in an AD mouse model (6). The known driving forces behind CSF clearance include cardiac output, vasocontractility, and CSF production, facilitated by aquaporin-4 function on egress channels (12).…”
Section: Csf Egress In Admentioning
confidence: 99%
“…However, their method does not distinguish between impaired membrane transport of Ab (4) and impaired CSF clearance, which carries the Ab. Suggesting CSF clearance abnormalities in AD, impaired glymphatic CSF clearance was recently observed in aged wild-type mice (5) and in an AD mouse model (6). The known driving forces behind CSF clearance include cardiac output, vasocontractility, and CSF production, facilitated by aquaporin-4 function on egress channels (12).…”
Section: Csf Egress In Admentioning
confidence: 99%
“…It has been demonstrated that there is an age-associated decline in glymphatic CSF influx, as well as interstitial solute clearance, including Aβ, and this appears to be related to reduced penetrating arterial pulsatility in the aged brain (58). In the context of Alzheimer’s disease (AD), young APP/PS1 double transgenic mice, expressing chimeric mouse/human amyloid precursor protein (Mo/HuAPP695swe) and a mutant form of human presenilin-1 (PS1-dE9), were found to have both reduced glymphatic influx and clearance of Aβ, and this was shown to worsen as a function of age (59). Further, pretreatment of wildtype mice with Aβ led to significant suppression of CSF tracer influx, suggesting that not only does AD lead to reduced glymphatic clearance and accumulation of Aβ, but that this Aβ aggregation will feed forward and produce further glymphatic slowing (59).…”
Section: The Glymphatic System – a Pathway For Csf-isf Exchangementioning
confidence: 99%
“…The importance of glymphatic clearance of interstitial solute is perhaps best demonstrated by the fact that its failure contributes to the pathophysiology of various CNS diseases. In the aged brain and in a murine transgenic model of Alzheimer's disease, glymphatic CSF influx is reduced and the clearance of Aβ is profoundly impaired (22,23). Interestingly, pretreating young wild-type mice with Aβ suppressed glymphatic influx, suggesting that not only is Aβ aggregation a consequence of a breakdown of flow within this pathway, but it may also be an independent cause of glymphatic dysfunction (23).…”
Section: The Glymphatic System: Anatomy and Function In Health And DImentioning
confidence: 99%
“…In the aged brain and in a murine transgenic model of Alzheimer's disease, glymphatic CSF influx is reduced and the clearance of Aβ is profoundly impaired (22,23). Interestingly, pretreating young wild-type mice with Aβ suppressed glymphatic influx, suggesting that not only is Aβ aggregation a consequence of a breakdown of flow within this pathway, but it may also be an independent cause of glymphatic dysfunction (23). Further, glymphatic impairment is a prominent feature of cerebrovascular disease, including both subarachnoid hemorrhage and multiple microinfarction (24,25).…”
Section: The Glymphatic System: Anatomy and Function In Health And DImentioning
confidence: 99%